2023
DOI: 10.1002/fft2.317
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of the anti‐colon cancer activity of cucurbitacin C from cucumber: A network pharmacological study and experimental validation

Jingke Liu,
Xiao Zhang,
Haixia Yang
et al.

Abstract: Colon cancer (CC) is a prevalent malignant tumor of the gastrointestinal tract and ranks among the leading causes of death in cancer patients worldwide. Cucurbitacin, a group of tetracyclic triterpenoids widely found in Cucurbitaceae plants, exhibits diverse pharmacological activities. However, the pharmacological activity of cucurbitacin C (CuC), a cucurbitacin derivative exclusively present in cucumbers, remains unclear. To investigate CuC's action targets and potential targets for CC, we utilized a database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…31 As a biological analysis method, network pharmacology can effectively collect and organize information on related proteins and targets, and provide a new method for the mechanistic study of traditional Chinese medicines. 32 Liu et al used network pharmacology to predict relevant targets of Gynostemma chamomin against anti-renal cell carcinoma. 33 It was found that Gynostemma chamomin induced the apoptosis of renal cell carcinoma through the PI3K/AKT/mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…31 As a biological analysis method, network pharmacology can effectively collect and organize information on related proteins and targets, and provide a new method for the mechanistic study of traditional Chinese medicines. 32 Liu et al used network pharmacology to predict relevant targets of Gynostemma chamomin against anti-renal cell carcinoma. 33 It was found that Gynostemma chamomin induced the apoptosis of renal cell carcinoma through the PI3K/AKT/mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%